Making community-based health planning and services work: Staffing, accountability and digital integration for quality primary health care in Northern Ghana - Dennis Chirawurah; Felix Achana; Abdou Orou-Seko; Joyce Aputere Ndago; Colette Santah; Vida Nyagre Yakong; Stephen Apanga; Martin Nyaaba Adokiya (PLoS ONE, 2026)
Background Strengthening primary health care through Ghana’s Community-based Health Planning and Services (CHPS) strategy depends on functional community structures, responsiveness, and integration into health information systems. However, the extent to which CHPS zones use the Ghana Community Scorecard (CSC) to promote accountability, equity, and service improvement remains unclear. We assessed CHPS staff categories and functionality in Northern region of Ghana and their ability to support Community Health Management Committees (CHMCs) in health facility assessments, Community Health Action Plans, and updating of results into existing digital platforms. Method A cross-sectional design combined quantitative surveys and qualitative interviews across 86 CHPS zones in six districts between March 13–20, 2024. Analysis focused on staff categories, functionality, CSC trainings, facility assessment, utilization of results, feedback mechanisms, and service improvements. Qualitative data explored barriers and enablers shaping CHPS performance. Results The 86 CHPS zones employed 549 health workers, predominantly female (51%). Categories included Community Health Officers (5%), midwives (17%), registered nurses (14%), enrolled nurses (33%), community health nurses (27%) and others (5%). Overall, 96% of CHPS zones were functional based on staff, CHMCs, volunteers, equipment, and service provision. About 88% had basic equipment. Services include outreach, home visits, minor illness treatment, antenatal care, and referrals. CSC training reached 41% of Community Health Officers and other health workers. Only 36% of the CHPS zones uploaded facility assessment results to existing digital platforms, and 46.5% implemented improvements from CSC recommendations. High-performing districts benefitted from adequate staffing, training, Non-Governmental Organization support, and community mobilization. Barriers included limited training coverage, exclusion of midwives and nurses from training, and persistent Gender, Equity and Social Inclusion (GESI) gaps. Conclusion CHPS zones show functionality but face challenges in staff capacity, training, and digital integration. Gaps in inclusivity and equipment provision limit effectiveness. Scaling-up training, strengthening human resources, improving basic equipment provision, and embedding GESI are essential to ensure CHPS zones deliver equitable, accountable, and quality services.